2005
DOI: 10.1007/s10764-005-0722-1
|View full text |Cite
|
Sign up to set email alerts
|

Ranging Patterns of Chimpanzees in a Montane Forest of Kahuzi, Democratic Republic of Congo

Abstract: I studied ranging patterns of a semihabituated unit-group of chimpanzees for 60 mo at Kahuzi. They had a total home range of 12.81 km 2 and a mean annual home range of 7.55 km 2 . Considering the low density of chimpanzees in the area vis-à-vis chimpanzees in arid areas, their home range is very small. Kahuzi chimpanzees used the home range in a clumped pattern, frequently visiting the core area and only rarely entering peripheral areas. The monthly range changes with fruit availability, increasing during peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…Fruiting phenology was partially coincident with flowering phenology and fruits were abundant during the dry season, in accordance with fruiting peaks documented at forest-dwelling chimpanzee sites with a unimodal rainfall pattern (Hockings et al 2009) or a bimodal rainfall pattern (Anderson et al 2005). In contrast, other forested sites characterized by either a unimodal (Basabose 2005;Tutin et al 1991) or bimodal (Chapman et al 1999;Moscovice et al 2007) pattern of rainfall showed fruiting peaks during the wet season, as also reported for a dry site with a unimodal precipitation pattern (Hernandez-Aguilar 2009). Despite this variation, our data indicate that the peak in ripe fruit abundance at LCNP occurs when conditions for .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Fruiting phenology was partially coincident with flowering phenology and fruits were abundant during the dry season, in accordance with fruiting peaks documented at forest-dwelling chimpanzee sites with a unimodal rainfall pattern (Hockings et al 2009) or a bimodal rainfall pattern (Anderson et al 2005). In contrast, other forested sites characterized by either a unimodal (Basabose 2005;Tutin et al 1991) or bimodal (Chapman et al 1999;Moscovice et al 2007) pattern of rainfall showed fruiting peaks during the wet season, as also reported for a dry site with a unimodal precipitation pattern (Hernandez-Aguilar 2009). Despite this variation, our data indicate that the peak in ripe fruit abundance at LCNP occurs when conditions for .…”
Section: Discussionsupporting
confidence: 53%
“…It is commonly assumed that frugivore biomass correlates with fruit abundance and fruit tree density, which highlights the importance of fruit availability in maintaining frugivorous primate populations (Stevenson 2001). Fruit availability varies among plant species, seasons, and study sites: at some sites ripe fruits are highly abundant during the wet season (Basabose 2005;Hernandez-Aguilar 2009;Suzuki 1969;Tutin et al 1997), whereas at other sites fruit abundance peaks during the dry season (Hockings et al 2009), or there is a bimodal pattern with peaks in both seasons (Watts et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…They are largely frugivorous when fruit is available, yet existing studies have reported that chimpanzees exhibit a number of adaptive responses to fruit scarcity. These responses include 1) shifting to lower quality, more abundant fallback foods, such as leaves, pith, and bark, during periods of low fruit availability Wrangham et al 1998); 2) altering feeding party or nest group size with varying fruit availability (Chapman et al 1995;Doran 1997;Furuichi et al 2001a;Itoh and Nishida 2007;Wrangham et al 1992); and 3) changing habitat use by traveling farther or into other areas to find food when fruit availability is low (Basabose 2005;Doran 1997). In fragmented habitats, altered plant species richness and abundance (Laurance et al 2002 may contribute to even more pronounced periods of fruit scarcity.…”
Section: Introductionmentioning
confidence: 99%
“…This variation has been attributed to variation in diet (Boonratana 2000;O'Brien and Kinnaird 1997), abundance and distribution of food resources (Basabose 2005;Curtis and Zaramody 1998;Robbins and McNeilage 2003), water availability (Scholz and Kappeler 2004), topographic factors (Furuichi and Hashimoto 2004), group size and population density (Strier 1987), intergroup encounters and availability of sleep sites (Buchanan-Smith 1991), as well as human disturbance (Glessner and Britt 2005). Among these, the spatial and temporal distribution and abundance of food resources are suggested to be the most important environmental determinants of primate range use (Basabose 2005;Clutton-Brock 1975;Harrison 1983;Isbell 1983;Newton 1992). In particular, temporal variation in the availability and distribution of preferred or major food resources shapes primate ranging patterns, and ultimately affects the size and shape of home range (Wallace 2006;Watts 1998).…”
Section: Introductionmentioning
confidence: 99%